LABORATORY AND FIELD EVALUATION OF ESSENTIAL OILS FROM Cymbopogon nardus AS OVIPOSITION DETERRENT AND OVICIDAL ACTIVITIES AGAINST Helicoverpa armigera Hubner ON CHILI PEPPER - Setiawati, Wiwin; Murtiningsih, Rini; Hasyim, Ahsol (Indonesian Agency for Agricultural Research and Development - MOA, 2011)
The fruit borer (Helicoverpa armigera Hubner) is one of the key pests of chili pepper in Indonesia. Yield loss due to this insect pest may reach up to 60%. Chemical treatment for con-trolling this insect pest is ineffective and eventually leads to environmental pollution. More environmentally safe insecticides are developed based on natural plant ingredients as their active compound such as essential oils. This study aimed to assess the potential of citronella oil for managing H. armigera on chili pepper. The experiments were conducted at the Indonesian Vegetables Research Institute from April 2009 to March 2010 and in Cirebon, West Java from November 2009 to March 2010. A field experiment was designed in a randomized complete block design with five treatments and replicated five times. Citronella oil was extracted by steam distillation from Cymbo-pogonÂ nardus. The oil was then chemically characterized by using GC-MS and its efficacy (ovicidal and feeding deterrent) against H. armigera was tested both in laboratory and field conditions. The GC-MS result showed that major chemical compounds of the citronella oil used were citronella (35.97%), nerol (17.28%), citronellol (10.03%), geranyle acetate (4.44%), elemol (4.38%), limonene (3.98%), and citronnellyle acetate (3.51%). The laboratory experiment revealed that the highest concentration (4,000 ppm) of citronella oil reduced egg laying by 53-66%. Ovicidal activity was concentration dependent, and egg hatchability decreased by 15-95% compared to control. The field experiment showed that treatment of citronella oil at 2.0 mL L-1 significantly reduced fruit damage by H. armigera similar to the plots treated with spinosad at the recommended dose (60 g ai ha-1). Application of citronella oil significantly reduced fruit damage by 72% and increased quality of the chili pepper. Because oviposition and feeding deterrent properties are key factors in controlling the pest, therefore this study revealed that citronella oil has potential to be incorporated into the controlling program of H. armigera on chili pepper.